PENGARUH KEPEMIMPINAN, BUDAYA KERJA, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA SELURUH KARYAWAN PT. PELINDO III CABANG TANJUNG EMAS SEMARANG) - Handoko, Wisnu Pratama; Hidayat, Wahyu; Suryoko, Sri (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
This research is motivated by globalization era that made a changed economy issued, like demands for economy actors to compete competitively. Every organization be charged to face every changed that happen responsively and can to equalize between external organization change and internal organitaion change. So that organization can adjust those changes. The purpose of this study was to determine the effect of leadership, work culture and compensation on employee performance of PT. Pelindo III Branch Tanjung Emas Semarang. This research method is explanatory, with data collection through questionnaires and interviews. The sampling technique used purposive technique sampling. The samples are 55 peoples whom are employees of PT. Pelindo III Branch Tanjung Emas Semarang. The analysis technique used was qualitative and quantitative. Quantitative analysis using validity, reliability, cross tabulation, correlation coefficient, coefficient of determination, simple and multiple regression analysis, as well as the significance test (t test and F test). The results of this study showed a relatively high level of kepemimpinan, but there are still residing in the medium category. Work culture is in good category, although there are still existing in the medium category. compensation is in good category, but there is still residing in the medium category. High employee performance, but still there are employees who have medium performance.All independent variables, named leadership (X1), work culture (X2), and compensation (X3) together (simultaneously) or individually (partial) affect employee performance dependent variable (Y). Advice can be given that the management of PT. Pelindo Branch Tanjung Emas Semarang need to give more attention to leadership that applied by general manager. Continously guidance need to apply for better performance of employee. And outbond activity need to present more to increase the teamwork. . Companies need to increase the compensation given to employees. This business can be done by providing the opportunity greater promotion and fees adjustment according to the hard work and dedication of the employees. The need for continued research by the company or outside the company regarding other variables that can provide additional contributions to improve employee performance.